The expansion of Acheulean hominins into the Nefud Desert of Arabia - Eleanor M. L. Scerri (Nature Portfolio, 2021)
Abstract The Arabian Peninsula is a critical geographic landmass situated between Africa and the rest of Eurasia. Climatic shifts across the Pleistocene periodically produced wetter conditions in Arabia, dramatically altering the spatial distribution of hominins both within and between continents. This is particularly true of Acheulean hominins, who appear to have been more tethered to water sources than Middle Palaeolithic hominins. However, until recently, chrono-cultural knowledge of the Acheulean of Arabia has been limited to one dated site, which indicated a hominin presence in Marine Isotope Stages (MIS) 7–6. Here, we report the first dated Acheulean site from the Nefud Desert of northern Saudi Arabia, together with palaeoecological evidence for an associated deep, probably fresh-water, lake. The site of An Nasim features varied and often finely flaked façonnage handaxes. Luminescence ages together with geomorphological and palaeoecological evidence indicates that the associated artefacts date to MIS 9. At present, An Nasim represents the oldest yet documented Acheulean sites in Arabia, and adds to a growing picture of regionally diverse stone tool assemblages used by Middle Pleistocene hominins, and likely indicative of repeated population re-entry into the peninsula in wet ‘Green Arabia’ phases.